1994
DOI: 10.1111/j.1476-5381.1994.tb17174.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord SP release and hyperalgesia in monoarthritic rats: involvement of the GABAB receptor system

Abstract: 1 Monoarthritis was induced in Lewis rats by interdermal injection in the left hind paw of a suspension of Mycobacterium tubercolusis in mineral oil (500 jig 100 IW'). Controls were injected with 100 fil mineral oil. 2 Withdrawal latencies to thermal stimuli of the inflamed paw, the contralateral and both paws of control rats were measured at daily intervals after injection by the plantar test. 3 After detection of the pain threshold, rat spinal cords were removed and horizontal dorsal slices were mounted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…An abrupt decrease in SP-ir in spinal perfusate was observed 1 week after CFA inoculation in the control rats without TENS, which is consistent with the findings obtained in spinal slices (58). Also, Sluka and Westlund (12) reported that during the acute experimental arthritis induced by injection of kaolin and carrageenan into the knee joint there was an initial depletion of SP contents in spinal dorsal horn, presumably because of a massive release of SP from the primary afferents.…”
Section: Resultssupporting
confidence: 90%
“…An abrupt decrease in SP-ir in spinal perfusate was observed 1 week after CFA inoculation in the control rats without TENS, which is consistent with the findings obtained in spinal slices (58). Also, Sluka and Westlund (12) reported that during the acute experimental arthritis induced by injection of kaolin and carrageenan into the knee joint there was an initial depletion of SP contents in spinal dorsal horn, presumably because of a massive release of SP from the primary afferents.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies indicate that a reduction in body weight can be used as an indirect measure of changes in feeding behavior that result from pain (Iadarola et al, 1988; Malcangio and Bowery, 1994), including tooth pain (Chudler and Byers, 2005). Therefore, in order to begin addressing the issue of behavioral relevance of our model, we have compared body weights of animals with active tooth pulp inflammation, as determined by the histological analysis, with sham-operated age-matched controls.…”
Section: Resultsmentioning
confidence: 99%
“…However, the GABA B system has a very low tonic activity in basal conditions, and only when the system is activated pharmacologically or by afferent stimulation, the antagonist effect becomes obvious (Bowery and Smart, 2006) as occurs, for example, in chronic pain (Malcangio and Bowery, 1994). For this reason, blocking GABA B receptors induces little effects on membrane properties, i.e., membrane potential or Ri (Lambert et al, 1989; Emri et al, 1996), so GABA B receptor antagonism would not explain all the effects induced by Aβ 25–35 .…”
Section: Discussionmentioning
confidence: 99%